2013
DOI: 10.1007/s00396-013-3103-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of adsorption affinity of polyacrylic acid for surfaces of mixed silica–alumina

Abstract: The influence of solution pH (in the range 3–9) on the adsorption of polyacrylic acid (PAA) on the mixed silica–alumina surface (SA-3: SiO2 97 %–Al2O3 3 % and SA-96: SiO2 4 %–Al2O3 96 %) was investigated. The following methods were applied in experiments: spectrophotometry, viscosimetry, potentiometric titration, and microelectrophoresis, which enable determination of adsorbed amount of the polymer, thickness of its adsorption layers, surface charge density, and zeta potential of solid particles in the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(63 citation statements)
references
References 24 publications
1
62
0
Order By: Relevance
“…The pKa of the PAAc carboxyl groups is ca. 4.5, but it can be higher as the PAAc polymerization degree increases [31]. The ionization of the carboxyl groups increases significantly at pH above pKa.…”
Section: Nanocomposites Characterizationmentioning
confidence: 96%
“…The pKa of the PAAc carboxyl groups is ca. 4.5, but it can be higher as the PAAc polymerization degree increases [31]. The ionization of the carboxyl groups increases significantly at pH above pKa.…”
Section: Nanocomposites Characterizationmentioning
confidence: 96%
“…7) suggest the dependency of the pH on the polymer efficiency. For instance, Wisniewska et al [42] have reported the effects of solution pH on the adsorption isotherms of polyacrylic acid (PAA) on mixed silica alumina, caused by the modification of surface charge density; Sparks et al [38] have reported the effect of pH on the energies of adsorption of PAA on calcite. Hence, the adsorption model could include such dependencies, in addition to temperature and polymer concentration.…”
Section: Model Limitations and Further Developmentmentioning
confidence: 98%
“…The higher the initial pH, the more PEI solution has to be added to reach the maximum turbidity. This can be explained based on the increasing concentration of deprotonated PAA carboxylic groups with increasing pH (p K a value about 4.5), resulting in an improved polyelectrolyte and polyelectrolyte complex solubility at low PEI concentrations. This is due to the presence of a larger number of acrylic acid groups which have to be saturated with PEI to build an insoluble polyelectrolyte complex.…”
Section: Resultsmentioning
confidence: 99%
“…Predominantly, the encapsulation of an enzyme in a polyelectrolyte complex is based on electrostatic interactions between opposite charges. Therefore, it is necessary to know the solution pH‐dependent overall charge of PEI and PAA which can be deducted from the p K a values of PAA (4.5) and PEI (7.9) . The used α‐amylase from B. licheniformis shows an isoelectric point of 4.4 (Supporting Information Figure S3), as determined based on the zero zeta potential and thus overall charge neutrality.…”
Section: Resultsmentioning
confidence: 99%